2022
DOI: 10.3390/atmos13122078
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Characterization with Long-Term AERONET Sun-Photometer Measurements in the Naples Mediterranean Area

Abstract: We report on the characterization of columnar aerosol optical and microphysical properties in the Naples Mediterranean area over a period of five years by the ground-based sun–sky–lunar photometer operating at our observational station in the frame of the AERONET network. Statistical and climatological analyses of daily mean values of aerosol optical depth at 440 nm (AOD440) and Ångström exponent at 440/870 nm (α440/870) allowed for highlighting their typical seasonal behavior. In particular, we observe higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Markowicz et al (2021), studied the climate interaction trends of aerosols distributed over Poland and their effects on incoming radiation fluxes, using a 10-year AERONET dataset [17]. Damiano et al (2022) characterized the columnar aerosol optical and microphysical properties to determine the prevailing aerosol type in the Naples Mediterranean area, using an AERONET dataset from a 5-year period [18]. AERONET and satellite datasets for a period of 16 years were also used by researchers to determine the annual variability of aerosol intrusion episodes in Morocco and the location's susceptibility to desert dust transport on a seasonal basis [19].…”
Section: Introductionmentioning
confidence: 99%
“…Markowicz et al (2021), studied the climate interaction trends of aerosols distributed over Poland and their effects on incoming radiation fluxes, using a 10-year AERONET dataset [17]. Damiano et al (2022) characterized the columnar aerosol optical and microphysical properties to determine the prevailing aerosol type in the Naples Mediterranean area, using an AERONET dataset from a 5-year period [18]. AERONET and satellite datasets for a period of 16 years were also used by researchers to determine the annual variability of aerosol intrusion episodes in Morocco and the location's susceptibility to desert dust transport on a seasonal basis [19].…”
Section: Introductionmentioning
confidence: 99%
“…Markowicz et al (2021), studied the climate interaction trends of aerosols distributed over Poland and their effects on incoming radiation fluxes, using a 10-year AERONET dataset [17]. Damiano et al (2022), characterized the columnar aerosol optical and microphysical properties to determine the prevailing aerosol type in the Naples Mediterranean area, using an AERONET dataset from a 5-year period [18]. AERONET and satellite datasets for a period of 16 years were also used by researchers to determine the annual variability of aerosol intrusions episodes in Morocco, and the location's susceptibility to desert dust transport on a seasonal basis [19].…”
Section: Introductionmentioning
confidence: 99%
“…The W-ICARB campaign [102] observed that a combination of different characteristics (sea and land, meteorology, air pollution, aerosol-mixing processes, e.g., coagulation, humidification) led to mean TAOD 500 and AE 470-870 values as high as 0.39 and 1.27, respectively. In the Naples area, Italy, Damiano et al [103] A last investigation concerns the type of aerosols present in the atmosphere of the Mediterranean in the period of the study. To categorise aerosols into groups, several researchers have developed varying ranges for the TAOD 550 and AE 470-870 values, e.g., [97,[104][105][106][107][108][109][110].…”
mentioning
confidence: 99%